2012
DOI: 10.5830/cvja-2012-048
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic patterns in treatment-naïve HIV-positive patients in Lagos, south-west Nigeria : cardiovascular topic - online article

Abstract: IntroductionCardiovascular abnormalities are common in HIV-infected patients, although often clinically quiescent. This study sought to identify by echocardiography early abnormalities in treatment-naïve patients.MethodsOne hundred patients and 50 controls with no known traditional risk factors for cardiovascular disease were recruited for the study. The cases and controls were matched for age, gender and body mass index. Both groups had clinical and echocardiographic evaluation for cardiac abnormalities, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Both systolic and diastolic dysfunctions are more common (∼30% prevalence) in PLHIV than in controls without HIV (65), and rarely, diastolic dysfunction is more prevalent (42,60). Ventricular dimensions and mass are large in PLHIV with HF in SSA, similar to findings from North America (65,76). Up to one-third of African HIV-infected children have LVSD (63,64).…”
Section: Epidemiology Of Hiv-associated Hf In Lmics In the Art Eramentioning
confidence: 99%
“…Both systolic and diastolic dysfunctions are more common (∼30% prevalence) in PLHIV than in controls without HIV (65), and rarely, diastolic dysfunction is more prevalent (42,60). Ventricular dimensions and mass are large in PLHIV with HF in SSA, similar to findings from North America (65,76). Up to one-third of African HIV-infected children have LVSD (63,64).…”
Section: Epidemiology Of Hiv-associated Hf In Lmics In the Art Eramentioning
confidence: 99%
“…Although ART has dramatically decreased the risk of opportunistic infections and mortality, there is mounting evidence that longstanding HIV infection and/or its treatment are associated with noninfectious complications, including cardiac disease [ 3 ]. Cardiac disease has been reported among treated and untreated HIV-infected adults, with prevalence ranging from 18 to 78% [ 4 , 5 ]. Low CD4 + cell count and high viral load have been identified as independent risk factors for cardiac disease, but residual confounding by well recognized traditional risk factors, such as smoking and hypertension remain an issue in these studies [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A smaller survey from Lagos, Nigeria, investigated the prevalence of cardiovascular disease in an HIV-positive cohort and found 1 patient of 100 patients to have HIV-PAH. 13 An ECHO study on 102 HIV patients presenting with cardiac symptoms in Tanzania revealed PH in 13% 14. PH with an RVSP>30 mm Hg was present in 4% of long-term survivors in a Zimbabwe cohort of vertically acquired HIV infection 15.…”
Section: Introductionmentioning
confidence: 99%